Unstable multipolarity? China's and India's challenges for global governance - John Humphrey; Dirk Messner (Deutsches Institut für Entwicklungspolitik (DIE), 2006)
Due to both their size and the enormous pace of their growth, China and India constitute a class of their own among the group of anchor countries. In the coming decades the stance that Europe adopts toward these Asian drivers of global change will be no less important than the state of transatlantic relations. At present Germany and Europe are not prepared to meet these challenges. The global governance debate that following the collapse of the Soviet Union took very little note at first of the rise of China and India. By now, attention is being paid to China, but in 15 years time India too will be an equally important economic player – and possibly even one with greater scope for global action, because it has a number of important comparative advantages over China (democracy, a balanced age pyramid). Gradually the contours of a multipolar system that is very likely to be marked by instability and turbulence are emerging. If the Asian drivers are not successfully integrated into a system of effective multilateralism, the world will be faced with a renewal of conflictual balance-of-power politics that would distract the efforts needed to contain the risks posed by globalization.
Keywords: 330